Makna Idiomatik Repetisi pada Kumpulan Puisi Perempuan Wali Kota Karya Suryatati A Manan - Zulfadhli, Muhammad (GERAM: Gerakan Aktif Menulis, 2017)
The study starts from the particularities owned the collection of poems Perempuan Wali Kota Suryatati A Manan. The specificity contained in the repetition of words in poetry. The repetition of a word or phrase in the poem expressed as reps. Repetition in a poem creates the aesthetic value of the poem. It is contained in a collection of poems Perempuan Wali Kota Suryatati A Manan. Through this study, the author examines the message delivered in a collection of poetry Women authors mayor expressed through repetition idiomatic meaning. Therefore, the assessment focused on the meaning of idiomatic repetition contained in a collection of poems Perempuan Wali Kota Suryatati A Manan. This is formulated problem is how the idiomatic meaning reps on a collection of poems Perempuan Wali Kota Suryatati A Manan. The purpose of this study is to explain and describe the meaning of idiomatic repetitions on a collection of poems Perempuan Wali KotaSuryatati A Manan. This research data is a letter, word, or phrase containing repetition. Source of research data derived from a collection of poems Perempuan Wali Kota Suryatati A Manan. The data collection was done by using the documentation. Data analysis was performed using the idiomatic meaning of the word at the role of repetition in the collection of poems Perempuan Wali Kota Suryatati A Manan works in construction. The results showed no repetition idiomatic meaning that the writer used to convey a message to the reader.